ANALISIS KINERJA KEUANGAN PADA PT SEJAHTERA ADHIGUNA MAKASSAR - L. Salusinus (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2008)
Financial performance of PT Sejahtera Adhiguna Makassar have been able to give maximal finance contribution. In the year 2007 economic condition uncertainty be marked downwards its purchasing power of people refering to governmental policy with raising of electricity tariff, phone and fuel where three sector this very have an in with macro economics. Company influence able to retake its market provenly of year advantage 2008 throuh increase in comparison with mount rate of interest going into effect public bank.